Febrile neutropenia in pediatric cancer patients in Northern Norway - Fundingsrud, Jonas Høylo (UiT Norges arktiske universitet, 2022)
Background: Febrile neutropenia in pediatric patients is a feared complication of both cancer and cancer treatment. With low levels of neutrophil granulocytes and toxic chemotherapy, patients are more prone to infections and the spreading of it. With low levels of neutrophils, systemic and local inflammatory symptoms are often weak, and fever may be the only symptom of both a life-threatening bloodstream infection, but also a harmless condition. Empirical antibiotics are the cornerstone of treatment, and information about microbiological trends are important for guiding empiric treatment. No validated prediction systems to differentiate between serious and harmless infections exist to date. Material and method: All pediatric oncologic patients in Northern Norway presenting with a fever of 38.5°C or higher, and a neutrophil count of less than 500 cells/mm3 in the period of 2010-2020 were included in the study. Laboratory values, treatment and clinical outcomes such as bacteremia, antibiotic treatment and etiology were obtained. Results: 232 episodes of febrile neutropenia occurred between 2010 and 2020. Blood cultures were only positive in 16.8% of episodes of FN. Gram-positive bacteria were most frequently detected. The most common gram-positive pathogens were viridans group-strepococci (25%). The gram-negative pathogens were E. coli (16.7%) and the moraxella group (4.2%). Antibiotic regimen of choice has shifted from ampicillins in combination with an aminoglycoside to piperacillin/tazobactam. A low white blood count at admission and a high maximum CRP level during an episode have a strong association to having a positive blood culture. Conclusion: No factors are able to predict the developing of sepsis, but many show associations with a higher risk of it. Microbiological etiology of febrile neutropenia has shifted in Northern Norway. The empirical antibiotic regimens of choice reflect recommendations in both international and national guidelines.